Individual Taxpayers Compliance and Strategy For Improvements - Tenrini, Rita Helbra; Nugroho, Anda (Jurnal Kajian Ekonomi dan Keuangan, 2014)
Everyone who has income above nontaxable threshold are required to register as a taxpayer. Indonesia has low rate o f registered taxpayer, only around 18 percent. This makes the tax revenue also low as the tax ratio is only 11 to 12 percent in the recent years. This figure is lower than its neighboring countries which has tax ratios above 14 percent Lower tax revenue makes it harder to finance public spending for the government, moreover, it could lead to budget deficits. This study analyzes the factors that influence the compliance o f taxpayer registration. The method used was descriptive quantitative approach. Micro data processing is conducted on National taxpayers database and household survey. The result shows that the characteristic o f taxpayers compliance determined by various factors such as business, industrial, sociological and regional. The extensification policy for taxpayers should be more focused on (i) individual taxpayers from non employee (individual entrepreneur); (ii) mining and construction sector; (iii) taxpayers with the age o f 41 years and above; (iv) provinces with low compliance, which are Gorontalo, Papua, West Nusa Tenggara, North Maluku and East Nusa Tenggara. The extensification must consider the potential tax payers o f each region and also human resource needs.